With gratitude from RHiME: Reviewers 2015 - RHiME, Editor (Research and Humanities in Medical Education, 2019)
The Editorial Board of RHiME would like to thank the following Reviewers for their outstanding contribution to the work of the journal. Without their dedication and the time they devoted to the evaluation of submissions made to RHiME, it would have been impossible to maintain the standards of the journal. Abha Khetarpal Anita Sikand Bakshi Apurba Rajbongshi Arun K Sharma Ashish Goel Balachandra V Adkoli Eishaan Kamta Bhargava Fouzia Shersad Himani Ahluwalia Jimmy Mathews Kiran Kaur Mary K Czerwiec Navjeevan Singh Radha Ramaswamy Satendra Singh Setu Gupta SG Kabra Shubhangi Vaidya Sudha Ramalingam Sunil Pandya Trveen Dhillon Vishal Sharma